Welcome to Children - A New Open Access Journal Dedicated to Sharing Medical Research Relevant to Children's Health - Sari Acra (MDPI AG, 2013)
I am very excited about the upcoming launch of Children, a journal dedicated to the streamlined yet scientifically rigorous electronic dissemination of peer-reviewed science related to childhood health and disease in developed and developing countries. The future of our world depends on the health and well-being of all its children. Thus, the global health issues facing children today will determine medical history. Unfortunately, as the world becomes more of a global information village in many respects, there have remained impediments to eliminating regional disparities in sharing health information, be it in the fields of infectious diseases, nutrition or cancer risks, to name but a few. It is my hope that Children will be a forum for sharing information, and engaging in discussions and dialogue relevant to the care of children, unimpeded by limitations imposed by traditional print media. We also hope to dedicate entire issues to timely and relevant single-topic publications. [...]